Disease profile and outcomes of neonates admitted to the paediatric intensive care unit at Red Cross War Memorial Children's hospital in Cape Town, South Africa - Riemer, Linda (Department of Paediatrics and Child Health, 2024)
Aim Neonatal healthcare is an area of focus in reducing global child mortality. Unwell neonates are usually managed in neonatal intensive care (NICU) but sometimes are admitted into paediatric units (PICU). This study aimed to describe the profile of neonates admitted to a South African PICU and to identify risk factors associated with mortality. Methods Patients with a post-menstrual age of <44 weeks, admitted to the PICU between November 2018 and October 2019, were included in a prospective observational study. Associations with mortality were evaluated with univariate and multivariable logistic regression analyses. Results 266 neonates (median birthweight 2210g (IQR 1397 – 2995g); chronological and post-menstrual age at admission 11 days (IQR 2 – 28) and 38 weeks (35 – 40) respectively were included, accounting for 18.4% of PICU admissions. The largest referral source were tertiary NICUs. Surgical admissions accounted for most patients. Congenital abnormalities occurred in 50.4% of the cohort. Neonatal mortality at ICU discharge was 10.9% compared to 3.8% in older patients (OR 3.08. CI 1.89 – 5.02; p = <0.001). Congenital abnormalities were the most common group of conditions associated with mortality, followed by NEC and infections. After logistic regression analysis the only variables independently associated with death/palliation were oscillatory ventilation, TPN and feeds received. Conclusion We describe a cohort of predominantly term and normal birth weight neonates but also includes expremature babies. Closer analysis of neonatal referral pathways can build on this study. All of this data can help policymakers and unit managers improve neonatal care.